Social catholicism and conservative feminism: María de Echarri and Dolors Monserdà - Velo Fabregat, Elisabet (UNIVERSITAS. Revista de Filosofía, Derecho y Política, 2021)
María de Echarri and Dolors Monserdà were two of the most significant figures of Catholic feminism of the early twentieth century. The press was one of the most important speakers for the dissemination of the ideas of both propagandists about the working situation of the workers, as well as the defense of Catholicism, which earned them a very important social and political relevance. This work will review some of his writings published in the press that will re-follow his social thinking, with the aim of embossing what his ideas were, attached to two ideological movements: conservative feminism and social Catholicism.
Keywords: History of Social Law; feminism; social catholicism; women press; catholic press